2019
DOI: 10.1021/acs.energyfuels.9b02586
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-Transform Infrared Proxies for Oil Source and Maturity: Insights from the Early Permian Alkaline Lacustrine System, Junggar Basin (NW China)

Abstract: Fourier-transform infrared (FTIR) spectroscopy has been widely applied in oil geochemical studies, particularly with respect to the physical properties and maturity of hydrocarbons. However, in general, it has been seldom used to investigate the organic matter (OM) depositional environment and source of oil. In this paper, we present such an FTIR spectroscopy study based on a case investigation in the early Permian alkaline–lacustrine-derived oils from the Mahu sag, Junggar Basin, Northwest China. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Recent exploration and exploitation indicate that the conglomerate reservoir of the Lower-Wuerhe Formation is now a field of exploration (Tao et al., 2019; Zhang et al., 2019). The main pore type in the conglomerate reservoir of the Lower-Wuerhe Formation in the Mahu Sag is primary intergranular pores, but dissolution pores such as inter-particle and intergranular dissolution pores are also developed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent exploration and exploitation indicate that the conglomerate reservoir of the Lower-Wuerhe Formation is now a field of exploration (Tao et al., 2019; Zhang et al., 2019). The main pore type in the conglomerate reservoir of the Lower-Wuerhe Formation in the Mahu Sag is primary intergranular pores, but dissolution pores such as inter-particle and intergranular dissolution pores are also developed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had demonstrated the capability of FTIR spectroscopy and microscopy for the identification of clay minerals in reservoir rocks, non-destructive and express analysis of the chemical structure, and distribution of organic matter in rocks, including the study of kerogen composition and its maturity in organic-rich shales for guiding regional oil exploration [55][56][57].…”
Section: Ftir In Hydrocarbon Explorationmentioning
confidence: 99%
“…Exploration and exploitation of tight oil are becoming increasingly important in the petroleum industry [1][2][3]. According to the macro-sedimentary environment of deposition, tight oil can be divided into marine and lacustrine facies [4,5]. Marine facies tight oil is important in North America and typically includes the Bakken and Eagle Ford resources [6][7][8].…”
Section: Introductionmentioning
confidence: 99%